PENGARUH RISIKO LIKUIDITAS DAN LEVERAGE TERHADAP KINERJA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010–2015 - Utami, Novia (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
This empirical study aims for examining the influence of liquidity risk on bank performance from the period 2010 to 2015 listed on Indonesia Stock Exchange. The measurement of liquidity risk will involve deposits or third-party fund, cash, and liquidity gap whereas the leverage will involve total debts to total assets as the independent variables. Meanwhile, the dependent variables of this study involve ROA and Tobin’s Q. This study was conducted under the purposive sampling method which involved 22 banks as samples. This study also used a panel data regression method and three testing models, including Common Effect Model, Fixed Effect Model, and Random Effect Model. The findings suggest a positive and significant influence of the third-party fund on ROA and Tobin’s Q. In contrast, the liquidity gap has a negative and significant influence on ROA and Tobin’s Q. Besides, the findings also suggest a positive and significant influence of cash on ROA and negatively significant on Tobin’s Q. The leverage has negative and significant influence on ROA and positively significant on Tobin’s Q.